Is early TMJ involvement in children with juvenile idiopathic arthritis clinically detectable? Clinical examination of the TMJ in comparison with contrast enhanced MRI in patients with juvenile idiopathic arthritis. Issue 1 (December 2015) - Keller, Heidi; Müller, Lukas; Markic, Goran; Schraner, Thomas; Kellenberger, Christian; Saurenmann, Rotraud
Abstract Background To test clinical findings associated with early temporomandibular joint (TMJ) arthritis in comparison to the current gold standard contrast enhanced magnetic resonance imaging (MRI) in children with juvenile idiopathic arthritis (JIA). Methods Seventy-six consecutive JIA patients were included in this study. Rheumatological and orthodontic examinations were performed blinded to MRI findings. Joint effusion and/or increased contrast enhancement of synovium or bone as well as TMJ deformity were assessed on MRI and compared to clinical findings. The maximal mouth opening capacity (MOC) of the JIA patients was compared to normative values obtained from a cohort of 20719 school children from Zürich, Switzerland. Results On MRI a total of 54/76 (71 %) patients and 92/152 (61 %) joints had signs of TMJ involvement. MRI showed enhancement in 85/152 (56 %) and deformity in 39/152 (26 %) joints. MOC, asymmetry and restriction in condylar translation showed significant correlation to TMJ enhancement and deformity, whereas antegonial notching was correlated with TMJ deformity only. When joints with deformity were excluded, enhancement alone did not show a significant correlation with any clinical factor. Conclusions Clinical findings in affected TMJs are correlated with structural damage only. Therefore clinical assessment of TMJs does not allow to diagnose early arthritis accurately and will still depend on contrast enhanced MRI.